Pentingnya Determinasi Diri Bagi School Well-Being Siswa SMP - Fauzi Rahman; Hafizh Zain Abdillah; Nurul Hidayah (Faculty of Ushuluddin and Humanities, 2020)
School well-being is important for students for optimal learning processes and personal development. This study aims to empirically examine how self-determination predicts school well-being in junior high school students in Yogyakarta using a linear regression analysis technique of 123 participants selected based on random cluster sampling. Measurements were made using 18 items of self-determination scale (Cronbach’s α = 0.83) and 30 items of school well-being scale (Cronbach’s α = 0.95). The results showed a regression coefficient (t = 2.062) with a significance level p = 0.041 (p < 0.05), which means that self-determination can predict the school well-being of junior high school students with an effective contribution of 5.17 percent.